2014
DOI: 10.1001/jamaophthalmol.2014.1008
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Tear Mucin 5AC in Office Workers Using Visual Display Terminals

Abstract: IMPORTANCE There are limited reports on the relationship between mucin 5AC (MUC5AC) concentrations in tears, working hours, and the frequency of ocular symptoms in visual display terminal (VDT) users. This investigation evaluated these relationships among patients with dry eye disease (DED) and individuals serving as controls. OBJECTIVE To determine the relationship between MUC5AC concentration in the tears of VDT users based on the diagnosis of DED and frequency of ocular symptoms. DESIGN, SETTING, AND PARTIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 26 publications
3
86
1
2
Order By: Relevance
“…"Computer vision syndrome" has been identified as increased evaporation of the tear film with prolonged blink interval and a large interpalpebral aperture [15], and decreased concentrations of secreted mucins (MUC5AC) which is a lubricant in human tears [16].…”
Section: Introductionmentioning
confidence: 99%
“…"Computer vision syndrome" has been identified as increased evaporation of the tear film with prolonged blink interval and a large interpalpebral aperture [15], and decreased concentrations of secreted mucins (MUC5AC) which is a lubricant in human tears [16].…”
Section: Introductionmentioning
confidence: 99%
“…In an institutional cross sectional study conducted among 96 participants of young and middle aged office workers in Japan, Uchino [19] observed that the prevalence of dry eye disease among computer users was 57%. Uchino used self-administered questionnaire as the instrument of study among his study participants.…”
Section: Discussionmentioning
confidence: 99%
“…The study suggests that office workers with prolonged VDT use, as well as those with an increased frequency of eye strain, have a low MUC5AC concentration in their tears. Furthermore, MUC5AC concentration in the tears of patients with Dry Eye Disease (DED) may be lower than that in individuals without DED [373]. It was also demonstrated that Neurturin (a neurotrophic factor for parasympathetic neurons)-deficient mice develop dry eye and keratoconjunctivitis sicca via reduction in MUC4 and 5 AC mucin and goblet cell density [374].…”
Section: Eye Dry Eye Disease (Ded)mentioning
confidence: 99%